STUDI PERBANDINGAN ANTARA TAMAN BACAAN MASYARAKAT “NGUDI KAWRUH” DAN “GUYUB RUKUN” DALAM PENINGKATAN LITERASI - Muhammad Solihin Arianto; Octia Putri Pamungkas (Pustakaloka, 2023)
This research is aimed to study how the comparison between the “Ngudi Kawruh” and “Guyub Rukun” Community Reading Centre in literation. The research method used in this research is interview, observation, and documentation. Data validity test in this research uses source and technique triangulation. Moreover, data analysis used is Miles and Huberman model. The research finds that the activities of literation in the “Ngudi Kawruh” Community Reading Centre are more than the “Guyub Rukun”  in terms of the 6 (six) dimensions of literation as mentioned in the theory. The “Ngudi Kawruh” meets all the 6 (six) dimensions of literation, meanwhile the Guyub Rukun only has 5 (five) dimensions of literation, those are reading and writing literation, science literation, digital literation, financial literation, and cultural and citizenship literation.